Community Structure of Cucumber (Holothuroidea) in Kakara Island Village Beach Subdistrict Tobelo - Herni Gasango; Gaspar D Manu; Jan FWS Tamanampo (Sam Ratulangi University, 2013)
Sea cucumbers are marine resources that have economically important value and one potential sufficient resources to serve nutritious meals so that the exploitation of this resource will continue to increase for food need. This can lead to changes in community structure. Sampling was done at night while the lowest ebb on August 20, 2013. The objective of this research work was to identity the species, the species to determine composition, and the population density and to know the species dominance, species diversity, and determine the form of interspecific association. Based on the results of research conducted in the District Tobelo Beach Island District Kakara Tobelo sea cucumber species found were 8 species, Holothuria atra, Actinopygia lecanora, Stichopus horrens, Bohadschia argus, Holothuria hilla, Actinopygia achinites, Holothuria pardalis, and Bohadschia marmorata. The diversity index H '= 1.9463, equity index or harmony e = 0.9359, and dominance index C = 0.1592. In addition, among 8 species associations if formed 9 pairs of positive associations and 19 pairs of negative associations. Â Keywords : Structure communities, Holothuroidea, Tobelo